Human rights in international criminal proceedings - Zappalà, Salvatore (O.U.P. OxfordGB, 2005)
Assumes that human rights law is the ideal lens for investigating the structures and functioning of international criminal justice. Analyses the structure of internatonal criminal proceedings - from the initiation of investigations to the enforcement of sentances - in order to establish how the protection of the rights of individuals operate.